Differentiate y=e^(x^2+2x)

For this question the chain rule should be used, the chain rule is that dy/du*du/dx=dy/dx.

If we say u=(x2+2x) and therefore y=eu

Then du/dx=2x+2 and dy/du=eu.

Then dy/du*du/dx= (2x+2)eu, then we can sub u back into the answer to obtain dy/dx=(2x+2)e(x^2+2)

Answered by Duncan F. Maths tutor

12726 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

The first term of an infinite geometric series is 48. The ratio of the series is 0.6. (a) Find the third term of the series. (b) Find the sum to infinity. (c) The nth term of the series is u_n. Find the value of the sum from n=4 to infinity of u_n.


If n is an integer prove (n+3)^(2)-n^(2) is never even.


Of the following 4 equations, 3 of them represent parallel lines. Which is the odd one out?


How do I show that (cos^4x - sin^4x) / cos^2x = 1 - tan^2x


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences